Gabapentin Pretreatment for Propofol and Rocuronium Injection Pain: A Randomized, Double-Blind, Placebo-Controlled Study - Cakirgoz, M. Y.; Demirel, I.; Duran, E.; Ozer, A. B.; Turkmen, U. A.; Ersoy, A.; Hanci, V. (Wolters Kluwer Medknow Publications, 2018)
Aim: This prospectively-planned, randomized, double-blind and placebo-controlled study aims to evaluate the effect of 1200 mg gabapentin premedication on the incidence and severity of propofol and rocuronium injection pain. Method: One hundred patients, between 18-60 years of age and ASA I-II for elective surgery planned under general anaesthetic, were randomized and divided into two groups. Two hours before the operation, the patients were given either a placebo tablet (Group P, n = 50) or 1200 mg gabapentin tablet (Group G, n = 50). On the back of the non-dominant hand, a vein was opened using a 20 G cannula , 0.9% NaCl was begun and preoxygenation was provided. For anaesthesia induction, 1% propofol at 800 ml/hr infusion rate was administered for 20 s. Propofol injection pain was evaluated up to the 20th second and recorded using a scale between 0 and 3 developed by McCrirrick and HunteR The remaining propofol dose (2.5 mg/kg), 5 ml saline and 0.6 mg/kg rocuronium were injected in that order over 10 seconds and rocuronium injection pain response was evaluated with a four point scale. Results: Pain after propofol infusion average score (degree >= 1) (Group G = 0.5; Group P = 1.0) and incidence (Group G = 46%; Group P = 68%); and average withdrawal movements response score linked to rocuronium injection pain (>= 1 response) (Group G = 0.3; Group P = 1.2) and incidence (Group G = 20%; Group P = 80%) were detected to be significantly lower in the gabapentin group compared to the placebo group (p < 0.001). Conclusion: Premedication with 1200 mg gabapentin 2 hours before propofol and rocuronium injection reduced the incidence and severity of injection pain.
Keywords: Gabapentin; injection pain; propofol; rocuronium